Physico-chemical parameters of the habitat of molluscs, intermediate hosts of schistosomes, in Kisangani and its surroundings - KANGANGA John Sapu; Médard Abedi Mwana Kimbulu; TEPUNGIPAME Alliance TAGOTO; Dadi Falay Sadiki; Joris Losimba Likwela; Thierry Bobanga Lengu (Orapuh Journal)
Introduction